Application of the child community health inclusion index for measuring health inclusion of children with disabilities in the community: a feasibility study - Paul Yejong Yoo; Annette Majnemer; Robert Wilton; Sara Ahmed; Keiko Shikako (BMC, 2023)
Abstract Background Participation in the community is a fundamental human right for children with disabilities and is a key component of their health and development. Inclusive communities can enable children with disabilities to participate fully and effectively. The Child Community Health Inclusion Index (CHILD-CHII) is a comprehensive assessment tool developed to examine the extent to which community environments foster healthy, active living for children with disabilities. Objectives To assess the feasibility of applying the CHILD-CHII measurement tool across different community settings. Methods Participants recruited through maximal representation, and purposeful sampling from four community sectors (Health, Education, Public Spaces, Community Organizations) applied the tool on their affiliated community facility. Feasibility was examined by assessing length, difficulty, clarity, and value for measuring inclusion; each rated on a 5-point Likert scale. Participants provided comments for each indicator through the questionnaire and a follow-up interview. Results Of the 12 participants, 92% indicated that the tool was 'long' or 'much too long'; 66% indicated that the tool was clear; 58% indicated that the tool was 'valuable' or 'very valuable'. No clear consensus was obtained for the level of difficulty. Participants provided comments for each indicator. Conclusion Although the length of the tool was regarded as long, it was seen to be comprehensive and valuable for stakeholders in addressing the inclusion of children with disabilities in the community. The perceived value and the evaluators' knowledge, familiarity, and access to information can facilitate use of the CHILD-CHII. Further refinement and psychometric testing will be conducted.